ANALISIS KEPUASAN TERHADAP PENGGUNAAN E-LEARNING MENGGUNAKAN TECHNOLOGY ACCEPTANCE MODEL DAN END USER COMPUTING SATISFACTION - Yulianingsih, Evi (Universitas Bina Darma, 2016)
Abstract: Information and communication technology is now used in every aspect of human life. In the educational use of Information and Communication is one of the factors in improving the quality of education. One form of the development of information technology and communication is e-learning. This study aimed to test the model acceptance of the use of E-Learning system at several universities in the city of Palembang by using a model of the Technology Acceptance Model (TAM) and End User Computing Satisfaction (EUCS). Tests will be carried out by using a calculation sttistik with tools SPPS application. Results of this study are expected to provide evidence empris about the factors that affect the acceptance (acceptance) the use of e-learning system using TAM model and EUCS. In addition the test results are also expected to provide evidence of the dominant factors affecting end user acceptance of the application of e-learning system Keywords: Technology Acceptance Model, End User Computing Satisfaction, e-learning, End User